Gaya Kepemimpinan Entrepreneurship Kepala Sekolah terhadap Mutu Lulusan - Hana Lestari; Hilyatul Hamidah; Ima Rahmawati (Jurnal Dirosah Islamiyah, 2022)
The purpose of this study was to identify and describe the contribution of entrepreneurship leadership to the quality of graduates in Vocational High Schools throughout Pamijahan District, Bogor Regency. The research method used in this study is a quantitative method using correlational techniques an analyzed using simple regression techniques. The results of the analysis contribution entrepreneurship leadership of the principal (X) to the quality of graduates (Y) in Vocational School throughout Pamijahan District, Bogor Regency which has been carried out by researchers, from the result of the questionnaire answers that have been distributed to 112 respondents using the SPSS version 21 program. Based on the test results Simple liniear Regression concluded that there was a positive an significant influence between the entrepreneurship leadership of the principal on the quality of graduates. Keywords: entrepreneurship leadership, Graduate Quality